Obscuring Our Sense of Morality: Barry Hallen’s Yoruba Moral Epistemology and the Problem of Character Indeterminacy - Babalola J. Balogun; Aderonke A. Ajiboro (The Thinker)
Barry Hallen’s critical engagements with the African (Yoruba) philosophical scholarship have earned him a place among African intellectual giants of the 20th century. Among his diverse contributions to African philosophical discourse is his Yoruba moral epistemology thesis. Built on his canonical distinction between knowledge (ìmọ) and belief (ìgbàgbọ) within the Yoruba linguistic framework, the Yoruba moral epistemology thesis suggests that knowledge of human character could be modelled alongside a similar pathway with knowledge of other propositional items where knowledge claims are made based on evidence obtained via first-hand information. Using Yoruba ethnological/linguistic resources as a methodological standpoint, our critique of Hallen’s Yoruba moral epistemology is primarily motivated by three fundamental observations: a. that the acclaimed distinction between ìmọ and ìgbàgbọ on which the thesis is based, is faulty; b. that the thesis does not agree to a certain conception of personhood within the Yoruba metaphysical worldview; and c. that the behaviourist implications engendered by Hallen’s Yoruba moral epistemology do not adequately represent the deeply spiritual essence of human conducts in Yoruba ethical system. We conclude that, although it is flawed, Hallen’s Yoruba moral epistemology thesis is an important contribution to African philosophy as it stimulates fruitful discussions around the subject matters of epistemology and ethics, and the connection between them within a traditional intellectual discourse of the Yoruba of Southwestern Nigeria.